2000
DOI: 10.1159/000029921
|View full text |Cite
|
Sign up to set email alerts
|

Use of Infrared Attenuated Total Reflectance Spectroscopy for the in vivo Measurement of Hydration Level and Silicone Distribution in the Stratum corneum following Skin Coverage by Polymeric Dressings

Abstract: The ability of wound dressings to hydrate the stratum corneum has been tested experimentally using attenuated total reflectance (ATR) infrared spectroscopy. A silicone gel dressing was able to hydrate the stratum corneum to the extent that its water content within the sampled volume was >60% after 5 h of contact compared with about 15% of normal exposed skin and about 30% for a highly permeable hydrophilic polyurethane dressing. An ATR method was devised to determine the presence and depth of penetration of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…There are several hypotheses that try to explain the efficacy of silicone sheeting in treating hypertrophic and keloid scars; several studies have gathered evidence supporting or refuting each, but no distinct mechanism has been defined. Possible mechanisms include increased temperature, 40 hydration caused by occlusion of the underlying skin, [41][42][43][44][45][46] increased oxygen tension, 47 direct action of the silicone oil, 44 and polarization of the Low-cross-link-density silicone is cross-linked through a polytetrafluoroethylene (PTFE) membrane, resulting in an interpenetrating polymer network (IPN), which has greater physical strength and durability than the low-crosslink-density silicone elastomer alone and retains its adhesive properties. 39 scar tissue caused by the negative static electric charge generated by movement of the silicone.…”
Section: Proposed Mechanisms Of Actionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are several hypotheses that try to explain the efficacy of silicone sheeting in treating hypertrophic and keloid scars; several studies have gathered evidence supporting or refuting each, but no distinct mechanism has been defined. Possible mechanisms include increased temperature, 40 hydration caused by occlusion of the underlying skin, [41][42][43][44][45][46] increased oxygen tension, 47 direct action of the silicone oil, 44 and polarization of the Low-cross-link-density silicone is cross-linked through a polytetrafluoroethylene (PTFE) membrane, resulting in an interpenetrating polymer network (IPN), which has greater physical strength and durability than the low-crosslink-density silicone elastomer alone and retains its adhesive properties. 39 scar tissue caused by the negative static electric charge generated by movement of the silicone.…”
Section: Proposed Mechanisms Of Actionmentioning
confidence: 99%
“…40,52,53 Hydration Effects Many investigators have studied the hydration effects of silicone elastomer sheeting on the stratum corneum. [41][42][43][44][45][46] Quinn and colleagues 44 have observed that, when applied to a scar, the treated skin area loses water via evaporation at a rate of half that of the untreated skin area. After removal of the silicone gel, the water loss from the underlying treated skin area increases significantly for a period of 15 to 20 minutes.…”
Section: Proposed Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infrared spectroscopy by attenuated total reflectance [13,28,29] and magnetic resonance imaging [30] are also very sensitive methods to assess the water content of the stratum corneum in vivo. In a series of dry skin conditions, the severity of the clinical aspect is also correlated with an altered permeability barrier function of the stratum corneum as assessed by an increased transepidermal water loss [31].…”
Section: Beyond Visual and Tactile Assessmentsmentioning
confidence: 99%